Management Considerations for Wheat Production in Florida - David L. Wright; Ann R. Blount; Ronald D. Barnett; Cheryl L. Mackowiak; James Marois (EDIS)
SS-AGR-289, a 3-page fact sheet by D.L. Wright, A.R. Blount, R.D. Barnett, C.L. Mackowiak and J. Marois, lists production practices for small grains in Florida, including field selection, crop rotation, tillage, variety selection, planting period, seeding rates and tilth, rows, weed control, fertility at planting, nitrogen and sulfur application, fungicides, irrigation, harvest, and economics. Published by the UF Department of Agronomy, October 2007.